A drug knowledge survey of two groups of ninth-grade students of Wagner High School, Clark Air Base, Philippines - Jackson, Charles J. ([Quezon City s.n.], 1972)
In order to better understand the present drug problem of the ninth grade students at Clark Air Base, a test was administered to a representative sample of 180 ninth graders to measure the existing drug knowledge.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Wagner High School, Clark Air Base -- Students; Narcotics; Narcotic habit